A fully degradable transcatheter ventricular septal defect occluder: Towards rapid occlusion and post-regeneration absorption. (December 2022) - Guo, Gaoyang; Hu, Jinpeng; Wang, Fan; Fu, Daihua; Luo, Rifang; Zhang, Fanjun; Hu, Cheng; Chen, Juan; Pan, Xiangbin; Yang, Li; Wang, Yunbing; Zhang, Xingdong
Abstract: Degradable heart occluders are a promising replacement for currently clinically used non-degradable ones without concerns about the complications caused by the persistent residue of a foreign implant. However, the inherent mechanical properties of degradable occluders are poor and decline with material degradation, leading to a preference for a long degradation period upon designing a degradable heart occluder. This configuration can lower the risk of occluder dislodgement but reduce the benefits of degradable implants over their non-degradable counterparts due to a longer retention of foreign materials in the human body. Here, we fabricated a fully degradable ventricular septum defect (VSD) occluder consisting of polydioxanone (PDO) fiber and poly-L-lactic acid (PLLA) membrane featuring an auto-locking function. The degradable occluder showed an excellent shape recovery effect after transcatheter delivery and anchored securely to a heart defect as evidenced by in vitro and in vivo experiments. The degradable occluder could warrant robust fixation ability during the first 3-months of implantation within which tissue reconstruction was accomplished and be completely absorbed within 12 months. Benefitting from these merits, the degradable occluder displayed desired occlusion and no complications after being implanted in the VSD sites of canines during a 24-months follow-up. Compared with traditional non-degradable occluders, our degradable occluder could provide a potentially superior approach for rapidly repairing the congenital VSD without interfering with the normal development and physiological function of the heart.